Market portfolios and mean/variance efficiency : evidence from Hong Kong, South Korea and Taiwan markets. - Yeo, Shi Yuan. (2011)
This paper extends Levy and Roll (2010)‟s study on the mean/variance efficiency of the market proxy to three market proxies in Asia – Hong Kong, Taiwan and South Korea, using data from 2001 to 2010. Utilizing sample parameters of the largest 100 stocks in each market, we performed an optimization to derive a set of adjusted parameters that make each of the proxy portfolios mean/variance efficient and tested the adjusted parameters for significant differences with their sample counterparts to infer efficiency. Our results show that the observed inefficiency is much greater in Hong Kong than Taiwan and South Korea, both of which are close to being efficient, and inefficiency was minimal across all three proxies when we decreased portfolio size to 50 stocks. Given that adjusted betas were largely similar to sample betas, our study also validates the practical usefulness of CAPM in estimating expected returns for the three markets.